Sistem Informasi Pelayanan Masyarakat Menggunakan Metode Agile berbasis Mobile - Meilino, Alwi; Utami, Wahyu Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Administrative services at the sub-district level often face obstacles, such as slow manual processes, long queues, and limited access to services. Conventional recording systems increase the risk of data errors and slow down the response to community needs. This study developed a mobile-based Public Service Information System with the Agile method to improve efficiency, transparency, and accessibility of services. This system allows residents to submit and track document status, access population information, and file complaints online through a mobile application. Key features include population data management, a digital queue system, and a performance monitoring dashboard. Development using an Agile approach allows for rapid iteration based on user feedback. Implementation was carried out in stages with staff training and outreach to the community. Evaluation results showed an increase in service efficiency with document processing times reduced by up to 40%. User satisfaction surveys showed that 85% of respondents felt that this system made it easier to access services and increased transparency. The main challenges include community digital literacy and technological infrastructure. With continuous improvement, this system is expected to become a model for other sub-districts in modernizing technology-based government administration.